2011
DOI: 10.3109/00365513.2011.591424
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial infarction induces early increased remote ADAM8 expression of rat hearts after cardiac arrest

Abstract: Remote histopathological changes of ischemic cardiac grafts are associated with increased expression of ADAM8 thus emphasizing a global myocardial impact of MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The association of this inflammatory change with myocardial tissue damage after heterotopic heart transplantation is already well observed in many previous studies. [28]…”
Section: Discussionmentioning
confidence: 99%
“…The association of this inflammatory change with myocardial tissue damage after heterotopic heart transplantation is already well observed in many previous studies. [28]…”
Section: Discussionmentioning
confidence: 99%
“…A modified heterotopic transplantation of the heart was performed to all 16 grafts, as previously described [4]. Briefly, before harvesting, cold 4 o C infusion with cardioplegia fluid (Custodiol ® ; Bretschneider HTK solution for cardioplegia and miltiorgan protection, Germany) was infused into the donor aorta in order to arrest the heart and maximize myocardial protection.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…This animal model mimics the clinical concept of having an area of local and persisting MI after complete revascularization of the globally ischemic heart. Using this experimental model, we have recently demonstrated that MI after IRI has a remote myocardial impact after cardiac arrest [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most members of ADAM families had been recognized to function in a range of biological processes, including myoblast differentiation and growth factor secretion 7, 8. Later on, several studies revealed that ADAM family also participated in cardiovascular development9, 10, 11, 12, 13 or cardiomyopathies 9, 14, 15, 16. Notably, a previous investigation suggested that ADAM10/12/15/17 expressions were increasing in both human dilated cardiomyopathy and (or) hypertrophic obstructive cardiomyopathy 17.…”
mentioning
confidence: 99%